The tyrosine kinase inhibitor nilotinib inhibits SARS‐CoV‐2 in vitro - Cagno, Valeria (Basic Clin Pharmacol Toxicol, 2020)
Since the emergence of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) at the end of 2019, no vaccine has been approved to counter this infection and the available treatments are mainly directed against the immune pathology caused by the infection. The coronavirus disease 2019 (COVID‐19) is currently causing a worldwide pandemic, pointing the urgent need for effective treatment. In such emergency, drug repurposing presents the best option for a rapid antiviral response. We assess here the in vitro activity of nilotinib, imatinib and dasatinib, three Abl tyrosine kinase inhibitors, against SARS‐CoV‐2. Although the last two compounds do not show antiviral efficacy, we observe inhibition with nilotinib in Vero‐E6 cells and Calu‐3 cells with EC50s of 1.44 μM and 3.06 μM, respectively. These values are close to the mean peak concentration of nilotinib observed at steady state in serum, making this compound a potential candidate for treatment of COVID‐19 in vivo.